Segmental Kyphosis After Cervical Interbody Fusion With Stand-alone Polyetheretherketone (PEEK) Cages. Issue 1 (February 2015) - Kim, Chi Heon; Chung, Chun Kee; Jahng, Tae-Ahn; Park, Sung Bae; Sohn, Seil; Lee, Sungjoon
<x xml:space="preserve">Abstract</x> Study Design: Retrospective comparative study. Objective: Two polyetheretherketone (PEEK) cages of different designs were compared in terms of the postoperative segmental kyphosis after anterior cervical discectomy and fusion. Summary of Background Data: Segmental kyphosis occasionally occurs after the use of a stand-alone cage for anterior cervical discectomy and fusion. Although PEEK material seems to have less risk of segmental kyphosis compared with other materials, the occurrence of segmental kyphosis for PEEK cages has been reported to be from 0% to 29%. There have been a few reports that addressed the issue of PEEK cage design. Method: A total of 41 consecutive patients who underwent single-level anterior discectomy and fusion with a stand-alone cage were included. Either a round tube–type (Solis; 18 patients, S-group) or a trapezoidal tube–type (MC+; 23 patients, M-group) cage was used. The contact area between the cage and the vertebral body is larger in MC+ than in Solis, and anchoring pins were present in the Solis cage. The effect of the cage type on the segmental angle (SA) (lordosis vs. kyphosis) at postoperative month 24 was analyzed. Results: Preoperatively, segmental lordosis was present in 12/18 S-group and 16/23 M-group patients (P=0.84). The SA was more lordotic than the preoperative angle in both groups just after surgery, with no difference between groups (P=0.39). At 24 months, segmental lordosis was observed in 9/18 S-group and 20/23 M-group patients (P=0.01). The patients in M-group were 7.83 times more likely than patients in S-group (P=0.04; odds ratio, 7.83; 95% confidence interval, 1.09–56.28) not to develop segmental kyphosis. Conclusions: The design of the PEEK cage used may influence the SA, and this association needs to be considered when using stand-alone PEEK cages.